Who Marries Whom on Silver Screen? Religion and Social Class in Marriage Patterns in Contemporary Indonesian Films - Nabhan F Choiron; Evi Eliyanah (Jurnal Studi Pemuda, 2020)
Popular culture, where cinema is part, is an important site where ideas of acceptable and unacceptable marriage pairing is confirmed and/or contested. In any cinema tradition, including Indonesian, romance films offer a rich site to investigate broader societal ideals around who should or should not marry whom. In this article, we report our study on conjugal pairing patterns in Indonesian blockbuster films produced and released between 2008 and 2018. We investigate how protagonists in the films decide whom they marry; this question then led us to critically examine the extent to which religion and social class shape marriage decisions. The findings show that marriage pairing patterns on Indonesian silver screen during the period are largely assortative; the characters in the selected films tend to marry people adhering to the same religion and belonging to the same social class as themselves. The increasingly visible trend of religious endogamy and the sustained trend of class homogamy are inseparable from the heightened Islamization in the post authoritarian era, the improving economic outlook at the macro and micro levels in the post Asian financial crisis, as well as the promotion of gender equality during the period.